Room temperature electrical properties and excitation performance of Al2O3 doped fused silica ceramics - Hajra, Sugato; Sahu, Manisha; Purohit, Varsa; Mohanta, Kalyani; Panigrahi, Basanta K.; Deepti, P.L. (Institute of Physics Publishing, 2019)
Al2O3 doped fused silica ceramic samples were synthesized by colloidal processing route. X-ray diffraction technique helped to give insight upon the phase formation of the synthesized samples. The dense growth of grains was depicted from surface micrographs. The frequency-dependent electrical properties of both sintered and quenched samples were examined from 100 Hz till 1 MHz. The frequency-dependent AC conductivity followed Jonscher's power law. The dielectric relaxation and Nyquist plot confirm the non-Debye nature in both sintered as well as quenched samples. The ferroelectric properties were depicted in the prepared samples. The sintered and quenched Al2O3 doped fused silica samples reveals that the samples get excited on the application of electric field and further can be utilized in filter application.
Keywords: conductivity; dielectric; impedance; silica